Green Positive Guidance and Green Positive Life Counseling for Decent Work and Decent Lives: Some Empirical Results - Di Fabio, Annamaria; Bucci, Ornella (Frontiers in Psychology, 2016)
This article discusses green positive guidance and green positive life counseling for decent work and decent lives. From a green guidance perspective, the connectedness to nature construct is important both in terms of the meaning of work and life construction. The study discussed in this article analyzed the relationship between empathy and connectedness to nature, controlling for the effects of fluid intelligence and personality traits. In this connection, the Advanced Progressive Matrices (APM), the Big Five Questionnaire (BFQ), and the Interpersonal Reactivity Index (IRI) were administered to 144 Italian high school students. The study revealed that connecteness to nature was not associated with fluid intelligence and was only moderately associated with personality traits. It was empathy that showed the highest association with connectedness to nature. The results open new opportunities for future research and interventions in green positive guidance/life counseling and green positive decent work.